EMA Review of Isatuximab in Combination with Pomalidomide and Dexamethasone for the Treatment of Adult Patients with Relapsed and Refractory Multiple Myeloma. (19th July 2021) - Delgado, Julio; Zienowicz, Malgorzata; Hennik, Paula Boudewina; Moreau, Alexandre; Gisselbrecht, Christian; Enzmann, Harald; Pignatti, Francesco
Abstract : : Isatuximab is a monoclonal antibody that binds to the human CD38 antigen. On May 30, 2020, a marketing authorization valid through the European Union (EU) was issued for isatuximab in combination with pomalidomide and dexamethasone (IsaPd) for the treatment of adult patients with relapsed and refractory (RR) multiple myeloma (MM). The recommended dose of isatuximab was 10 mg/kg, administered intravenously weekly at cycle 1 and then biweekly in subsequent 28-day cycles. Isatuximab was evaluated in a phase III, open-label, multicenter, randomized trial that randomly allocated IsaPd versus pomalidomide plus dexamethasone (Pd) to adult patients with RR MM. The primary endpoint of the trial was progression-free survival, as assessed by an independent review committee, which was superior for the IsaPd arm (hazard ratio, 0.596; 95% confidence interval, 0.436–0.814; p = .001) compared with the Pd arm. Treatment with IsaPd led to higher incidences of treatment-related adverse events (AEs), grade ≥ 3 AEs, and serious AEs compared with Pd treatment. Most frequently observed AEs that occurred more often in the IsaPd arm were infusion-related reactions, infections, respiratory AEs, neutropenia (including neutropenic complications), and thrombocytopenia. The aim of this article is to summarize the scientific review of the application leading to regulatory approval in the EU. Implications for Practice: Isatuximab was approved in the European Union, in combination with pomalidomide and dexamethasone, for the treatment of patients with multiple myeloma who have already received therapy but whose disease did not respond or relapsed afterward. The addition of isatuximab resulted in a clinically meaningful and significant prolongation of the time from treatment initiation to further disease relapse or patient's death. The safety profile was considered acceptable, and the benefit-risk ratio was determined to be positive. Abstract : This article summarizes the scientific review of the application leading to EMA regulatory approval of isatuximab combination therapy for multiple myeloma.